REGIONAL DIVERSITY OF ENGLISH AND DIALECT LEVELING IN CONTEMPORARY ENGLAND (Scientific journal of the Fergana State University, 2026)
This article examines the regional dialects of the English language in England and current trends in their development. The aim of the study is to characterize the main dialect zones the North, the Midlands, and the South and to identify processes of dialect leveling and the emergence of new urban vernaculars. The material is based on dialect survey data and recent sociolinguistic studies. Descriptive and comparative-analytical methods were used. As a result, key features of northern, central, and southern dialects were highlighted, and it was found that under the influence of migration and the media, differences are being leveled out, for example, the spread of southern pronunciation norms northward, although some regions retain unique features. The emergence of new multicultural urban sociolects, e.g., Multicultural London English, is also observed. The scientific and practical significance of accounting for dialectal variation is discussed, including for language teaching and translation.